2018
DOI: 10.1002/jcb.27070
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs C2dat1 enhances vascular smooth muscle cell proliferation and migration by targeting MiR‐34a‐5p

Abstract: Deregulated proliferation of vascular smooth muscle cells (VSMCs) is one common phenomenon of atherosclerosis progression. Long noncoding RNAs (lncRNAs) are one group of noncoding RNAs that play essential roles in many cell biological processes, including cell development, growth, and migration. However, the role of a novel calcium/calmodulin-dependent protein kinase type II subunit delta (CAMK2D)-associated lncRNA, CAMK2D-associated transcript 1 (C2dat1), in VSMCs is still uncovered. In this study, we showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…9 Another study reported that lncRNA-C2dat1 enhances VSMC proliferation and migration by targeting miR-34a-5p. 11 In previous work, we demonstrated that calcification/senescence of VSMCs is regulated by the lncRNA-ES3/miR-34c-5p/BMF axis. 12 However, that study did not elucidate the specific role of lncRNA-ES3 in calcification/senescence of VSMCs, and the overall mechanism remained largely uncharacterized.…”
Section: Introductionmentioning
confidence: 93%
“…9 Another study reported that lncRNA-C2dat1 enhances VSMC proliferation and migration by targeting miR-34a-5p. 11 In previous work, we demonstrated that calcification/senescence of VSMCs is regulated by the lncRNA-ES3/miR-34c-5p/BMF axis. 12 However, that study did not elucidate the specific role of lncRNA-ES3 in calcification/senescence of VSMCs, and the overall mechanism remained largely uncharacterized.…”
Section: Introductionmentioning
confidence: 93%
“…14,15 In addition, SIRT1 plays an important protective role in the cardiovascular system through its functions on STAT3 deacetylation. [10][11][12][13][14][15] A study revealed that atherosclerosis in SIRT1 +/-Apo E −/− mice is decreased significantly compared with ApoE −/− counterparts. 10 SIRT1 can also suppress AngII-induced VSMCs proliferation and migration as well as phenotypic transformation, counteracting hypertensive angiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is an important inhibitory factor of AngII-induced VSMCs phenotypic transformation as well as proliferation and migration, acting by decreasing STAT3 acetylation and phosphorylation. [10][11][12][13][14][15] Therefore, we further explored whether WWP2 promotes STAT3 acetylation and phosphorylation by inhibiting the effect of SIRT1 on STAT3. As expected, co-immunoprecipitation assays results showed that WWP2 overexpression decreased the interaction between SIRT1 and STAT3 ( Figure 2E), whereas WWP2 knockdown increased the interaction between SIRT1 and STAT3 ( Figure 2F).…”
Section: Wwp2 Forms a Complex With Sirt1-stat3 Competing For The Imentioning
confidence: 99%
“…LncRNA C2dat1 is a CaMK2D-associated transcript 1. LncRNA shows higher expression in CAD ( 90 ). C2dat1 binds to miR-34a and modulates its expression in CAD.…”
Section: Noncoding Rnas That Sponge Mirnas Involved In Aging and Regementioning
confidence: 99%
“…C2dat1 binds to miR-34a and modulates its expression in CAD. Overexpression of C2dat1 suppresses miR-34a expression and upregulates its target protein SIRT1, increasing VSMC growth and migration in CAD ( 91 ).…”
Section: Noncoding Rnas That Sponge Mirnas Involved In Aging and Regementioning
confidence: 99%